The mediating role of social goals in the relationships between teachers’ transformational leadership, prosocial climate, and motor self-efficacy in physical education students - Reigal, Rafael E.; Morales-Sánchez, Verónica; Matos, Rui; Hernández-Mendo, Antonio (Frontiers in Psychology, 2025)
BackgroundThere is a limited body of research explaining the associations between transformational leadership and prosocial climate, particularly when considering social goals as mediating variables. Furthermore, no studies have explored the mediating effect of social goals and prosocial climate in the relationships between transformational leadership and motor self-efficacy.PurposeThe aim of this study was to examine the relationships between transformational leadership, social goals, prosocial climate, and the perception of motor self-efficacy. Specifically, this research intends to determine the mediating role of social goals in the relationships between teacher transformational leadership, prosocial climate, and motor self-efficacy in Physical Education students.MethodThe study involved 392 adolescents (52.81% male, n = 207; 47.19% female, n = 185) aged between 14 and 16 years (M = 15.07; SD = 0.78), who were secondary school students in various educational institutions in the city of Málaga (Spain). Data were collected using the Transformational Teaching Questionnaire, the Social Goals in Physical Education Scale, the School Prosocial Climate Questionnaire, and the Motor Self-Efficacy Scale.ResultsThe results revealed multiple relationships among the studied variables. Specifically, a mediation effect of social goals was observed between transformational leadership and prosocial climate, as well as a mediation effect of social goals and prosocial climate in the relationship between transformational leadership and motor self-efficacy.ConclusionThese findings suggest an association between transformational leadership, prosocial climate, and motor self-efficacy, highlighting the importance of social goals as key variables in understanding these relationships.